2008
DOI: 10.1111/j.1432-2277.2008.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pre-kidney-transplant risk factors and post-transplant cardiovascular events and death

Abstract: Summary The prevalence of cardiovascular risk factors in renal transplant candidates is high. A better understanding of the relation between these risk factors and cardiovascular morbidity and mortality is mandatory to improve transplantation outcome. In this retrospective cohort study 2187 adult patients who received a first kidney transplant between 1984 and 1997 were included. We analyzed the incidence of post‐transplant cardiovascular events and tried to identify independent pretransplant risk factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 23 publications
7
44
1
2
Order By: Relevance
“…Humoral immunity attacks allografts by producing specific antibodies against the grafts [20][21][22][23][24]. In addition, pre-existing conditions, such as diabetes mellitus, [25,26], hypertension [27,28], cardiovascular conditions [29,30], infections [31][32][33], malignancy [34][35][36], were all factors that affect the outcomes and survival of transplant grafts. Once a pathological process begins, renal allografts express and release protein molecules at different levels or patterns compared with their physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immunity attacks allografts by producing specific antibodies against the grafts [20][21][22][23][24]. In addition, pre-existing conditions, such as diabetes mellitus, [25,26], hypertension [27,28], cardiovascular conditions [29,30], infections [31][32][33], malignancy [34][35][36], were all factors that affect the outcomes and survival of transplant grafts. Once a pathological process begins, renal allografts express and release protein molecules at different levels or patterns compared with their physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction is important because perioperative risk stratification has traditionally focused on identifying patients with undiagnosed or unstable CAD as a way to reduce the risk of MACEs after surgery. In a retrospective study of 2187 transplant recipients, Aalten et al 84 reported independent associations of recipient age, diabetic nephropathy, claudication, and prior cardiac events with an increased risk of cardiac events (defined as MI, coronary revascularization, stroke, or cardiac death) within the first 3 months after kidney transplantation.…”
Section: Considerations For Kidney Transplantation Candidates With DImentioning
confidence: 99%
“…The incidence of CVD amongst transplant recipients is estimated to be 4.7-40 % at 3 years post-transplant [ 15 , 16 ]. A long-term study of renal transplant recipients documented a 40 % cumulative incidence of CVD at 10 years post-transplant [ 17 ].…”
Section: Prevention and Treatment Of Cardiovascular Disease In Renal mentioning
confidence: 99%